VD_FINDINFO Décision / 2011 / 186 vom 2. Mai 2011 - VD Tribunal cantonal (2011)
RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET, DÉPENS, DROIT D'OBTENIR UNE DÉCISION, DROIT D'ÊTRE ENTENDU, PROCÈS ÉQUITABLE | 56 al. 2 LPGA, 91 LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD